Cerebrospinal Fluid Analysis Post–COVID‐19 Is Not Suggestive of Persistent Central Nervous System Infection. Issue 1 (22nd November 2021) - Schweitzer, Finja; Goereci, Yasemin; Franke, Christiana; Silling, Steffi; Bösl, Fabian; Maier, Franziska; Heger, Eva; Deiman, Birgit; Prüss, Harald; Onur, Oezguer A.; Klein, Florian; Fink, Gereon R.; et al.
Abstract : This study was undertaken to assess whether SARS‐CoV‐2 causes a persistent central nervous system infection. SARS‐CoV‐2–specific antibody index and SARS‐CoV‐2 RNA were studied in cerebrospinal fluid following COVID‐19. Cerebrospinal fluid was assessed between days 1 and 30 (n = 12), between days 31 and 90 (n = 8), or later than 90 days (post–COVID‐19, n = 20) after COVID‐19 diagnosis. SARS‐CoV‐2 RNA was absent in all patients, and in none of the 20 patients with post–COVID‐19 syndrome were intrathecally produced anti–SARS‐CoV‐2 antibodies detected. The absence of evidence of SARS‐CoV‐2 in cerebrospinal fluid argues against a persistent central nervous system infection as a cause of neurological or neuropsychiatric post–COVID‐19 syndrome. ANN NEUROL 2022;91:150–157